Maternal alcohol consumption and socio-demographic determinants of neurocognitive function of school children in the rural Western Cape - Viglietti, Paola (Department of Public Health and Family Medicine, 2021)
Background. Within the South African context there is a large body of research regarding the associations between maternal gestational drinking and diagnosable child FASDs. However, there remains a paucity of local research regarding the impacts of other kinds of maternal drinking behaviours (e.g. past and present maternal drinking) and related socio-demographic factors on developmentally sensitive areas of child neurocognitive functioning, such as executive functioning (EF). Methods. This study was cross-sectional in design, utilising a gender balanced sample of N=464 children between the ages of 9.00 and 15.12 (year.months) in three rural areas within the Western Cape. Information regarding maternal drinking behaviours (before, during and after pregnancy) and related socio-demographic factors was collected via structured interviews with mothers or proxy respondents. Six subtests from the Cambridge Automated Neuropsychological Battery (CANTAB), were used to assess three aspects of child EF namely: (1) processing speed, assessed by the MOT and RTI subtests, (2) attention, assessed by the MTT and RVP subtests and (3) memory, assessed by the SWM and PAL subtests. Findings. For all three maternal alcohol use behaviours examined, there was an apparent non-significant trend whereby children of mothers who reported alcohol use (before, during and after pregnancy) performed worse (on average) than children of mothers reporting non-alcohol use on the EF subtests. Several of the socio-demographic factors were found to act as significant predictors of subtest specific EF performance including child sex (RTI: B=.46, p<. 01; MTT: B=.05, p<.05), child age (RTI: B=.27, p<.05; MTT: B=.11, p<.01), home language (MOT: B=- .13, p<.05), maternal employment (MTT: B=-.04, p<.05) and household size (SWM: B=-1.29, p<.05). Conclusions. These study findings provide initial insights into the impacts of different types of maternal drinking behaviours and related socio-demographic factors on child EF outcomes within the context of an LMIC, South Africa.